Care transitions and social needs: A Geriatric Emergency care Applied Research (GEAR) Network scoping review and consensus statement. (23rd August 2021) - Gettel, Cameron J.; Voils, Corrine I.; Bristol, Alycia A.; Richardson, Lynne D.; Hogan, Teresita M.; Brody, Abraham A.; Gladney, Micaela N.; Suyama, Joe; Ragsdale, Luna C.; Binkley, Christine L.; Morano, Carmen L.; Seidenfeld, Justine; et al.
Abstract: Objectives: Individual‐level social needs have been shown to substantially impact emergency department (ED) care transitions of older adults. The Geriatric Emergency care Applied Research (GEAR) Network aimed to identify care transition interventions, particularly addressing social needs, and prioritize future research questions. Methods: GEAR engaged 49 interdisciplinary stakeholders, derived clinical questions, and conducted searches of electronic databases to identify ED discharge care transition interventions in older adult populations. Informed by the Protocol for Responding to and Assessing Patients' Assets, Risks, and Experiences (PRAPARE) framework, data extraction and synthesis of included studies included the degree that intervention components addressed social needs and their association with patient outcomes. GEAR convened a consensus conference to identify topics of highest priority for future care transitions research. Results: Our search identified 248 unique articles addressing care transition interventions in older adult populations. Of these, 17 individual care transition intervention studies were included in the current literature synthesis. Overall, common care transition interventions included coordination efforts, comprehensive geriatric assessments, discharge planning, and telephone or in‐person follow‐up. Fourteen of the 17 care transition intervention studies in older adults specifically addressed at least one social need within the PRAPARE framework, most commonly related to access to food, medicine, or health care. No care transition intervention addressing social needs in older adult populations consistently reduced subsequent health care utilization or other patient‐centered outcomes. GEAR stakeholders identified that determining optimal outcome measures for ED–home transition interventions was the highest priority area for future care transitions research. Conclusions: ED care transition intervention studies in older adults frequently address at least one social need component and exhibit variation in the degree of success on a wide array of health care utilization outcomes.